The nodal tensor model for QoS estimation of communications networks - Ponomarev, D. (ХНУРЭ, 2013)
The main characteristics of QoS are estimated usually by methods of queuing theory. However, in the application to nets queuing theory considers processes for each of the systems (switches, routers, servers etc.) without taking into account the network topology. On the other hand, graph theory uses the topology for network analysis but cannot consider arrival and service processes in network systems. Tensor analysis of networks allows to provide an estimate of QoS characteristics with taking into account both the arrival and service processes and the network topology. This work presents the nodal tensor model as a tool for QoS analysis in the communications networks. In these models, the main systems of the communications network represented as single - line queuing systems (but and other types of queuing systems can be used). Models formed in accordance to the types of networks. The proposed models allow estimating the QoS characteristics for the individual routes and the entire network. Moreover, these models can be used to optimize the communications networks.